2017
DOI: 10.1111/1759-7714.12444
|View full text |Cite
|
Sign up to set email alerts
|

Deguelin inhibits epithelial‐to‐mesenchymal transition and metastasis of human non‐small cell lung cancer cells by regulating NIMA‐related kinase 2

Abstract: BackgroundNon‐small cell lung cancer is a lethal malignancy with a high mortality rate. Deguelin displays an anti‐tumor effect and inhibits metastasis in various cancers. The aberrant expression of NIMA‐related kinase 2 (NEK2) indicates poor prognosis and induces epithelial‐to‐mesenchymal transition (EMT) and metastasis processes. However, the underlying mechanism between deguelin and NEK2 has remained elusive.Methods NSCLC cell lines were treated with deguelin. Wound‐healing and invasion assays were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Rotenone has been reported to target NF-κb to induce EMT reversion and apoptosis in pancreatic cancer (16). In addition, rotenone can prevent the metastasis and EMT of human non-small cell lung cancer cells by modulating NIMA-related kinase 2 (18). However, the effects and underlying mechanisms of rotenone on cc metastasis and EMT require further study.…”
Section: Rotenone Restrains Colon Cancer Cell Viability Motility Andmentioning
confidence: 99%
“…Rotenone has been reported to target NF-κb to induce EMT reversion and apoptosis in pancreatic cancer (16). In addition, rotenone can prevent the metastasis and EMT of human non-small cell lung cancer cells by modulating NIMA-related kinase 2 (18). However, the effects and underlying mechanisms of rotenone on cc metastasis and EMT require further study.…”
Section: Rotenone Restrains Colon Cancer Cell Viability Motility Andmentioning
confidence: 99%
“…NEK2 has also been shown to be involved in abnormal cell differentiation, tumor proliferation, drug resistance, and poor prognosis in several kinds of tumors. [37][38][39] A lot of effort has been made to understand the functional role of NEK2 in cancer. Zhang et al found that NEK2 significantly enhanced the invasive ability of HCC cells, and epithelial-mesenchymal transition played a pivotal role in the NEK2-mediated promotion of HCC cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, deguelin impedes carcinogenesis by 1) inducing cell apoptosis, 2) inhibiting tumor cell propagation, and 3) preventing malignant transformation of tumors. 16,17 Crucial oncogenic pathways likely targeted by deguelin are the phosphoinositide 3-kinase (PI3K)/Akt pathway, [18][19][20][21][22][23][24][25][26] the Wnt signaling pathway, 27,28 the epidermal growth factor receptor (EGFR) and c-Met signaling pathway, 29 the epithelial-to-mesenchymal transition (EMT) pathway, 30 the hedgehog signaling pathway, 31,32 and angiogenesis-related pathways. 33 In addition, deguelin has been identified as an Aurora B kinase inhibitor that exhibits a potent antitumor effect in human esophageal squamous cell carcinoma.…”
Section: Key Proliferative and Angiogenic Pathways Targeted By Deguelinmentioning
confidence: 99%
“…51 Since 2008, it has been widely accepted that EMTs can occur in 3 distinct biological backdrops, which lead to distinct functional consequences. 52 Deguelin has been demonstrated to act via the inhibition of EMT pathways in non-small cell lung cancer (NSCLC) cells 30 and to inhibit the metastasis of pancreatic tumors via increased expression of E-cadherin, a tight junction protein that prevents tumor dissemination (metastasis). 53 Liu et al 54 found that low-dose deguelin significantly inhibited the invasion and migration of oral cancer cells while being associated with minimal cytotoxicity and systemic toxicity.…”
Section: Preventing Metastasismentioning
confidence: 99%